Physico-chemical characteristics of ground water samples from different areas of Thrissur District, Kerala State, India - Thambi, Mity; Cherian, Tom; Jose, Anju Therese; Jamal, Sunaina (International Journal of Environment, 2015)
The analysis of groundwater quality of important town areas of Thrissur district was carried out during the pre-monsoon period of 2014. The Physicochemical and biological parameters such as temperature, turbidity, electrical conductivity, total dissolved solid, pH, alkalinity, chloride, salinity, total harness, calcium, magnesium, iron, phosphate, sulphate, dissolved oxygen, biological oxygen demand, chemical oxygen demand, total coliform count and E. coli were determined. Most of the physicochemical parameters were observed above the desirable limit but below the permissible limit of drinking water standards of World Health Organization (WHO). Total coliform bacteria count values of different samples are within the permissible limit. The studies reveal that samples from Thrissur town (T), Guruvayoor (G) and Laloor (L) shows the presence of E.coli bacteria. All other samples were negative for E.coli bacteria. Dumping of wastes near road sides, flood due to heavy rains, improper waste management in hospitals, markets, flats etc increases the pollution of ground water. The results were compared with WHO guidelines, 2006 and Bureau of Indian Standards (IS: 10500, 1991) desirable limits for drinking water. DOI: http://dx.doi.org/10.3126/ije.v4i2.12636 International Journal of Environment Vol.4(2) 2015: 182-192